Seepage Analysis for Construction, with Applications to Some Projects in Hong Kong. (13th February 2021) - Cheng, Y. M.; Chen, Fu; Zhu, Zhen; Yuan, Changfeng; Li, Liang
Abstract : Deep excavations are intensively carried out in many cities in China and other countries. One of the major loadings in such construction work is the water pressure, and great effort is required to assess the seepage problem and the corresponding water pressure on the retaining wall for a good design and construction. Different methods used for the seepage analysis are discussed in this paper through a series of projects in Hong Kong. Some interesting phenomena from the seepage analysis will also be discussed. Two large scale seepage field tests in Hong Kong are also used for the illustration of the back analysis in seepage problems which are seldom carried out. The comparative studies demonstrate that a realistic seepage analysis is very important for deep excavation works, but it was not seriously considered in the past.